2019
DOI: 10.1002/pon.5307
|View full text |Cite
|
Sign up to set email alerts
|

Protection motivation theory in predicting cervical cancer screening participation: A longitudinal study in rural Chinese women

Abstract: Objective To examine factors longitudinally associated with cervical cancer screening uptake among rural Chinese women, guided by protection motivation theory (PMT). Methods A large sample of women (n = 2408, aged 35‐65 years old) was randomly selected from a rural county in China in 2015 and followed up for 2 years. Data for demographic factors, knowledge of cervical cancer screening, screening outcome, and six PMT constructs measured at the baseline in 2015 were used to predict cervical cancer screening part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…Another PMT predictor of women’s intention to undergo screening was perceived severity, which was in accordance with previous studies [ 32 , 45 ]. A quasi-experimental study in Iran suggested that women are more likely to perform the screenings if they understand the severity and harm of the disease as well as the related consequences [ 46 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Another PMT predictor of women’s intention to undergo screening was perceived severity, which was in accordance with previous studies [ 32 , 45 ]. A quasi-experimental study in Iran suggested that women are more likely to perform the screenings if they understand the severity and harm of the disease as well as the related consequences [ 46 ].…”
Section: Discussionsupporting
confidence: 90%
“…Protection motivation theory (PMT) was proposed by Rogers based on HBM in 1975 [ 27 ]. It is a cognitive social theory used to predict various health behaviors, such as schistosomiasis prevention [ 28 ], vaccination behavior [ 29 ], and cancer screening [ 30 , 31 , 32 ]. PMT considers threat appraisal and coping appraisal as the main predictors of health behavior [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“… Model Basic premise Example studies Health Belief Model ( Rosenstock, 1974 ) Behaviour result of beliefs about: perceived susceptibility; perceived severity; benefits and barriers; cues to action Wardle et al, 2000 , Yarbrough and Braden, 2001 , Orbell et al, 1996 Theory of Reasoned Action ( Ajzen and Fishbein, 1980 ), Theory of Planned Behaviour ( Ajzen, 1991 ) Behaviour result of attitudes, subjective norm, and perceived behavioural control* predicting intention and then behaviour. *can directly impact behaviour Cooke and French, 2008 , Orbell et al, 2006 , Drossaert et al, 2003 , Rutter, 2000 , Devellis et al, 1990 Protection Motivation Theory ( Rogers, 1975 ) Behaviour determined by threat appraisal and coping appraisal including key components of: perceived severity; perceived susceptibility; response efficacy and self-efficacy Orbell and Sheeran, 1998 , Li et al, 2020 Precaution adoption process model ( Weinstein and Sandman, 1992 ) Stage model explaining how a person decides to take action and how that decision translates into action Costanza et al, 2005 , Costanza et al, 2009 , Ferrer et al, 2011 , Marlow et al, 2018 Transtheoretical Model ( Prochaska and DiClemente, 1982 ) Stage model synthesising 18 therapies to elicit and maintain behaviour change. Key stages include: pre-contemplation; contemplation; preparation; action; maintenance Rakowski et al, 1996 , Lipkus et al, 1996 , Trauth et al, 2003 , Kelaher et al, 1999 Social Cognitive Theory ( Bandura, 1986 ) An extension of Social Learning Theory proposing a dynamic and reciprocal interaction of the person, environment, and behaviour.…”
Section: Approach To Model Developmentmentioning
confidence: 99%
“…The PMT plays an important role in explaining and predicting the protection willingness and behaviours of individuals. [25][26][27][28][29] In terms of behavioural interventions, PMT-based interventions can increase the occurrence of benign behaviours by improving individual cognitive levels. 30 31 The information-motivation-behavioural skills (IMB) model, which was first proposed by Fisher et al 32 in their study of high-risk behaviours for HIV, has been applied to explain and predict the healthy lifestyle of adolescents 33 34 and the adherence to medication of patients with rare diseases.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…The PMT plays an important role in explaining and predicting the protection willingness and behaviours of individuals. 25–29 In terms of behavioural interventions, PMT-based interventions can increase the occurrence of benign behaviours by improving individual cognitive levels. 30 31 …”
Section: Introductionmentioning
confidence: 99%